EP636 Assessing the impact of clinicopathological prognostic variables on survival outcome in patients with clear cell endometrial carcinoma: an institutional analysis. (1st November 2019) - Dimopoulou, S; Thomakos, N; Sotiropoulou, M; Ntzeros, K; Vlachos, DE; Haidopoulos, D; Liontos, M; Bamias, A; Rodolakis, A
Abstract : Introduction/Background: Endometrial clear cell carcinomas (ECCC) are rare but aggressive subtype of uterine carcinomas. Several clinicopathological characteristics have been associated with poorer prognosis. The aim of this study is to determine the value of different clinicopathological parameters in predicting prognosis. Methodology: We retrospectively analyzed files of ECCC patients treated in our institution between 2005 and 2015. Clinicopahtological data and survival outcomes were collected. Our data were analyzed using Cox regression analysis. Results: Fifty- two patients with ECCC and mean age 65.7 years (range 38–90) were analyzed. Myometrial invasion >50% was present in 59.6% of the cases. Adnexal involvement, lymph node-pelvic and paraortic- metastasis and extra uterine metastasis were present at 21.2%, 7.7%, 17.3 and 32.7%, respectively. Cervical involvement was found in 34.6% of the patients. All patients received adjuvant treatment. The mean follow up period was 6.6 years.13.5% of the cases appeared with recurrent disease. Advanced stage (III and IV), positive peritoneal cytology, paraortic node involvement, extra uterine metastasis and omentum involvement were significantly associated with greater hazard for relapse in univariate Cox regression analysis. Mutlivariate analysis revealed that aortic node metastasis (p=0.013) and omentum involvement (p=0.030) were independent predictors of relapse. 63.4% of the patients were alive at 5 years. Advanced stage, peritoneal cytology, adnexal involvement, aortic node and extra uterine metastasis, omentum and vaginal involvement were associated with worse survival in univariate analysis, while in multivariate analysis peritoneal cytology (p=0.045), adnexal involvement (p=0.036) and aortic node metastasis (p=0.035) were independently associated with survival. Type of adjuvant treatment did not affect prognosis. Conclusion: Our study suggests that adnexal, omentum and vaginal involvement in addition to aortic node, extra uterine metastases, peritoneal cytology and stage are predictive factors of worse prognosis. Disclosure: Nothing to disclose.